SNORD80-guided 2’-O-methylation stabilizes the lncRNA GAS5 to regulate cellular stress responses - Liang Xu; Xiao Hong Zhao; Yuan Yuan Zhang; Meng Yao Zhang; Long Yue Zhang; Kai Hong Ye; Liu Teng; Man Man Han; Yi Meng Yue; Jiezhen Yang; Rachel Ogle; Jacob Netherton; et al. (Proceedings of the National Academy of Sciences, 2025)
The introns of the gene encoding the long noncoding RNA (lncRNA) GAS5 host up to 10 C/D box small nucleolar RNAs (snoRNAs). However, whether there is a regulatory and functional relationship between these snoRNAs and GAS5 is unknown. Here, we show that the expression of SNORD80, but not the other snoRNAs, parallels GAS5 expression and is regulated alongside GAS5 in response to cellular stress. The 2′-O-methylation at the A496 site, located within a segment of GAS5 complementing the conserved RNA-binding region on SNORD80, promotes GAS5 stability and consequent upregulation. This methylation requires SNORD80, as it is diminished by knockdown of SNORD80 and increased by SNORD80 overexpression, similar to the effects of manipulating the expression of fibrillarin, the methyltransferase of the box C/D small nucleolar ribonucleoprotein particle (snoRNP). The upregulation of SNORD80 in response to cellular stress is due to an enhancement in its stability, which is associated with an increase in its interaction with fibrillarin. Collectively, these results identify a role for SNORD80 in guiding 2′-O-methylation to stabilize GAS5. This uncovers a feedforward regulatory loop at the GAS5 gene locus in response to cellular stress and sheds light on posttranscriptional mechanisms governing lncRNA expression.